2021
DOI: 10.52082/jssm.2021.635
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Muscle Loss in the Abdomen and Anterior Thigh in Elderly Males with Locomotive Syndrome

Abstract: Although locomotive syndrome (LS) is a condition of reduced mobility, little information is available regarding the loss of site-specific skeletal muscle mass. The aim of the present study is to examine site-specific muscle loss in elderly males with LS. A total of 100 men ranging in age from 65 to 74 years were divided into two groups (LS and non-LS) using LS risk tests including the stand-up test, two-step test, and the 25-question geriatric locomotive function scale Muscle thickness (MTH) at eight sites—ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Therefore, it could be possible that LS was not associated with muscle mass and SMI using bioelectrical impedance analysis in older individuals aged around 70 years. Recently, Natsume et al [34] reported that the muscle thickness of the anterior thigh and rectus abdominis was significantly lower in older men with LS, and the reduction in site-specific muscle mass significantly correlated to LS-related physical functions. Previous studies on LS also demonstrated that 10 m gait speed and muscle strength of the legs were significantly lower in the older adults with LS than in those without [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be possible that LS was not associated with muscle mass and SMI using bioelectrical impedance analysis in older individuals aged around 70 years. Recently, Natsume et al [34] reported that the muscle thickness of the anterior thigh and rectus abdominis was significantly lower in older men with LS, and the reduction in site-specific muscle mass significantly correlated to LS-related physical functions. Previous studies on LS also demonstrated that 10 m gait speed and muscle strength of the legs were significantly lower in the older adults with LS than in those without [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review demonstrated the importance of trunk muscle strength for balance, functional performance, and fall prevention in older adults [53]. In addition, muscle cross-sectional ( [54] and muscle thickness values ( [27] of the rectus abdominis are related to functional ability in older adults. Trunk exercise training improves the size of trunk muscles, trunk muscle strength and physical function [53,55].…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding changes in speci c muscle groups have been shown to occur independently of those of appendicular lean tissue mass, as determined by dual-energy X-ray absorptiometry (DXA) [25]. In addition, some studies have reported that the age-related loss in the size of speci c muscle groups is associated with that in lower extremity performance [25][26][27]. For example, [25,26] reported that the thigh anterior to posterior ratio in muscle thickness is negatively correlated with age [25] and with zig-zag walking time in older men and women [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation